The effectiveness of self-directed learning (SDL) for teaching physiology to first-year medical students - Pai, Kirtana M (Australas Med J, 2014)
BACKGROUND: Self-directed learning (SDL) has become popular in medical curricula and has been advocated as an effective learning strategy for medical students to develop competence in knowledge acquisition. AIMS: The primary aim was to find out if there was any benefit of supplementing self-directed learning activity with a traditional lecture on two different topics in physiology for first-year medical students. METHOD: Two batches of first-year Bachelor of Medicine and Bachelor of Surgery (MBBS) (Batch A and Batch B) comprising 125 students each, received an SDL session on Morphological classification of anaemia. The students belonging to Batch A received a one-hour lecture on the same topic three days prior to the SDL session. The students were given a 10 multiple choice questions (MCQ) test for a maximum of 10 marks immediately following the SDL session. The next topic, Conducting system of the heart, disorders and conduction blocks was taught to both batches in traditional lecture format. This was followed by an SDL session on the same topic for Batch A only. The students were evaluated with a MCQ test for a maximum of 10 marks. RESULTS: The mean test scores on the first topic were 4.38±2.06 (n=119) and 4.17±1.71 (n=118) for Batch A and Batch B, respectively. The mean test scores on the second topic were 5.4± 1.54 (n=112) and 5.15±1.37 (n=107) for Batch A and Batch B, respectively. There was no significant difference between the groups. CONCLUSION: For first-year medical students, SDL is an effective teaching strategy for learning physiology. However, no additional benefit is gained by supplementing SDL with a lecture to facilitate learning physiology.